FEATURES OF ENTERPRISE ECONOMIC SECURITY PROVISION: COMPLIANCE APPROACH - YAREMENKO, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article analyzes the state of economic security of domestic enterprises under martial law, identifies the main threats to their activity, outlines the main direct and indirect consequences of the influence of active hostilities on ensuring the economic security of economic entities. The need to change approaches to ensuring their effective functioning is determined, namely the expediency of using a compliance approach at industrial enterprises regarding the functioning of achieving sustainable development of an industrial enterprise, achieving a system of goals (social, economic, environmental, etc.) is substantiated. It was established that profit, as the ultimate goal of activity, loses its priority value. It becomes only one of the economic goals and fulfills the functional task of a means of achieving the system of enterprise goals. Not only traditional components (economic, social, environmental), but also indicators of economic security become important during the reconstruction and transformation of the development of the enterprise. A possible approach to the identification of a security component is to take into account an important factor - compliance-security, the use of which at the enterprise level determines the protection of its vital interests from external and internal violations of regulatory legal acts, standards, founding and internal documents of the enterprise by means of identification, assessment and maximum reduction (elimination) of compliance destroyers.
Keywords: economic security; compliance approach; goal system; compliance security; destructors